Analysis of the dynamics of environmental movements in France; Emphasizing the concept of ecological citizenship - maryam yari estahbanati; Bahare Sazmand (رهیافتهای سیاسی و بین المللی)
Introduction and objectives: This article examines how environmental movements in France interact with their global counterparts and emphasizes the importance of cross-border cooperation and shared responsibility in addressing environmental challenges. Also, by clarifying the transnational dimensions of environmental actions in France, it seeks to highlight the interconnectedness of environmental issues beyond borders and support a transnational and collaborative approach to environmental sustainability. By examining transnational environmental practices, valuable insights are provided into the effectiveness of transnational strategies and their impact on shaping practices of ecological citizenship on a global scale. The main goal of this research is to analyze how environmental movements in France interact with their surroundings, especially in transnational dimensions. Using Andrew Dobson's ecological citizenship theory, this study aims to shed light on the importance of cross-border cooperation, solidarity and collective responsibility in addressing global environmental challenges.Materials and methods: Through a qualitative research approach, this study provides the necessary framework to examine the dynamics, strategies and outcomes of transnational environmental actions in France. The analysis method used in this research is content analysis, which deals with the nuances of Dobson's ecological citizenship theory applied to environmental movements in France and provides a comprehensive analysis of the narratives and discourses surrounding transnational environmental projects. A systematic review of the textual data increases the understanding of how ecological citizenship is conceptualized and implemented in the French context and illuminates the role of communication and discourse in shaping transnational environmental activist practices. By using content analysis methods, it is tried to discover and understand the complex relationships between language, environmental values ​​and collective action in the field of ecological citizenship in France.Findings: This research critically examines the existing literature to understand Dobson's ecological citizenship theory and its relevance in the French environmental landscape. The findings of the research emphasize the fundamental transnational dimensions inherent in environmental movements in France. These movements not only recognize environmental issues that transcend national boundaries, but also support international cooperation to effectively address them. Emphasis on cross-border cooperation, solidarity and shared responsibility appear as key themes in addressing global environmental concerns in the field of French environmental activities. In addition, this research highlights the interconnected nature of environmental challenges and the importance of joint efforts in reducing their impact on a global scale. These findings underscore the importance of strengthening cross-border partnerships and collective action to tackle pressing environmental issues facing both France and the international community. By advocating shared responsibility and solidarity across borders, environmental movements in France exemplify an active approach towards sustainability and environmental stewardship.Conclusion: This study shows the pivotal role of transnational cooperation and ecological citizenship in the formation of environmental movements in France. Recognizing the importance of international cooperation and shared responsibility, these movements demonstrate a proactive approach to addressing environmental challenges on a global scale. This study contributes to a detailed understanding of ecological citizenship in the French context and emphasizes the importance of cross-border solidarity in fostering sustainable environmental practices.